Single Nucleotide Polymorphisms in HOTAIR Are Related to Breast Cancer Risk and Prognosis in the Northeastern Chinese Population - Lv, Zheng; Kou, Changgui; Chen, Naifei; Jia, Lin; Sun, Xu; Gao, Yangyang; Bai, Rilan; Yang, Ming; Cui, Jiuwei (Frontiers in Oncology, 2021)
Background: The long noncoding RNA HOX transcript antisense RNA (HOTAIR) is highly expressed in breast cancer (BC) tissues and is associated with the recurrence and metastasis of BC. Until now, the results of studies on associations between several functional single nucleotide polymorphisms(SNPs) (rs920778, rs1899663, and rs4759314) in HOTAIR with BC susceptibility carried out in different regions of China are still inconsistent. There is no study on correlation between HOTAIR SNPs and prognosis of Chinese population. Therefore, we investigated the relationship between HOTAIR SNPs and susceptibility to and prognosis of BC. Method: We conducted a population-based case-control study involving 828 BC cases and 905 healthy controls. Peripheral blood DNA was used for genotyping. The association between HOTAIR genotypes and BC risk were estimated by odds ratios (ORs) computed using the binary logistic regression model. The relationships between HOTAIR SNPs and clinicopathological features were tested by Pearson’s chi-square test or Fisher’s exact test. Survival was analyzed using the Kaplan-Meier method. Results: The functional rs920778 genetic variant increased BC risk in the codominant model. Individuals with the rs920778 GG genotype had an OR of 2.426 (95% confidence interval [CI] = 1.491–3.947, P < 0.001) for developing BC compared to individuals with the AA genotype. Individuals with the AG genotype had an OR of 1.296 (95% CI = 1.040–1.614, P = 0.021) for developing BC compared to individuals with the AA genotype. Individuals with the rs4759314 GA genotype had a lower BC risk than individuals with the rs4759314 AA/GG genotype (OR = 0.566, 95% CI = 0.398–0.803, P = 0.001). The rs1899663 genotype had no correlation with BC susceptibility. Haplotypes composed of rs920778–rs1899663 and rs920778–rs1899663–rs4759314 could increase BC risk (all P < 0.001). There were no statistically significant associations between HOTAIR SNPs and clinicopathological characteristics. The rs920778 GG/AG genotypes were associated with worse disease-free survival (DFS) (p = 0.012), and the rs4759314 GA genotype was associated with worse DFS and overall survival (OS) (p = 0.011). Conclusion: HOTAIR SNPs(rs920778 and rs4759314) are significantly related to BC susceptibility and prognosis in the northeastern Chinese population, indicating the significance in the occurrence and development of BC.